2015
DOI: 10.1016/j.bbamem.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and the dietary protein/carbohydrate ratio regulate the expression of SNAT2 amino acid transporter in the mammary gland during lactation

Abstract: The sodium coupled neutral amino acid transporter 2 (SNAT2/SAT2/ATA2) is expressed in the mammary gland (MG) and plays an important role in the uptake of alanine and glutamine which are the most abundant amino acids transported into this tissue during lactation. Thus, the aim of this study was to assess the amount and localization of SNAT2 before delivery and during lactation in rat MG, and to evaluate whether prolactin and the dietary protein/carbohydrate ratio might influence SNAT2 expression in the MG, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Whereas, FAA levels seem to be independent of the mothers' age (64), maternal body-mass index is reported to slightly influence levels of several FAAs (65,66). Mechanisms underlying this effect are not known, but may involve the hormone prolactin, as prolactin is involved in regulating FAA transport in the mammary gland and levels of prolactin associate with maternal body-mass index (67)(68)(69). Studies investigating the effect of maternal diet on the AA composition in human milk indicate that the TAA composition is largely independent of the AA composition of the diet (70,71).…”
Section: The Faa Composition In Human Milk Is Dynamic and Seemingly Rmentioning
confidence: 99%
“…Whereas, FAA levels seem to be independent of the mothers' age (64), maternal body-mass index is reported to slightly influence levels of several FAAs (65,66). Mechanisms underlying this effect are not known, but may involve the hormone prolactin, as prolactin is involved in regulating FAA transport in the mammary gland and levels of prolactin associate with maternal body-mass index (67)(68)(69). Studies investigating the effect of maternal diet on the AA composition in human milk indicate that the TAA composition is largely independent of the AA composition of the diet (70,71).…”
Section: The Faa Composition In Human Milk Is Dynamic and Seemingly Rmentioning
confidence: 99%
“…In rat mammary gland, PRL has an important role in the regulation of AA uptake (Viña et al, 1981). The sodiumcoupled neutral amino acid transporter 2 (SNAT2) is characterized as a classical system A transporter and is important for the uptake of small neutral AA into the mammary gland to promote cell proliferation during gestation and to induce milk protein synthesis during lactation (Velázquez-Villegas et al, 2014). Studies in mammary gland explants from lactating rats have demonstrated that PRL treatment increases SNAT2 mRNA and protein abundance (Velázquez-Villegas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The sodiumcoupled neutral amino acid transporter 2 (SNAT2) is characterized as a classical system A transporter and is important for the uptake of small neutral AA into the mammary gland to promote cell proliferation during gestation and to induce milk protein synthesis during lactation (Velázquez-Villegas et al, 2014). Studies in mammary gland explants from lactating rats have demonstrated that PRL treatment increases SNAT2 mRNA and protein abundance (Velázquez-Villegas et al, 2015). In the current study, we found that mRNA levels of LAT1 in cultured mammary epithelial cells of dairy cows were increased with increasing concentrations of PRL and peaked at 5 μg/mL PRL.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine is contained in large amounts in milk, especially in the colostrum [ 25 ]. It has been reported that the mRNA of amino acid transporters is expressed in the mammary gland [ 2 , 28 ] and that their transporters transfer free amino acids from maternal blood to milk. The large amount of taurine in the milk seems to derive from 1) maternal blood via taurine transporters, and 2) the mammary glands.…”
Section: Discussionmentioning
confidence: 99%